Peter Blokhuis - Heidi Daamen - Theo Daamen - Maarten Van Dreven - Jan Grotenbreg - Jurjen De Haan - Richard Hefti - Nan Hoover - Douglas James Johnson - Johan Jorna - William Lindhout - Marcel Maeyer - Walter Nobbe - Fabrizio Plessi - Paul Van Rafelghem - Maus Slangen - Douglas Swan - Walter Tafelmaier - Leo De Vries - Friso Wiegersma - Troels Worsel. (Amsterdam : Galerie Jurka Amsterdam, 1976)
Blokhuis, Peter ; Daamen, Heidi ; Daamen, Theo ; Van Dreven, Maarten ; Grotenbreg, Jan ; De Haan, Jurjen ; Hefti, Richard ; Hoover, Nan ; Johnson, Douglas James ; Jorna, Johan ; Lindhout, William ; Maeyer, Marcel ; Nobbe, Walter ; Plessi, Fabrizio ; Van Rafelghem, Paul ; Slangen, Maus ; Swan, Douglas ; Tafelmaier, Walter ; de Vries, Leo ; Wiegersma, Friso ; Wörsel, Troels
Peter Blokhuis - Heidi Daamen - Theo Daamen - Maarten Van Dreven - Jan Grotenbreg - Jurjen De Haan - Richard Hefti - Nan Hoover - Douglas James Johnson - Johan Jorna - William Lindhout - Marcel Maeyer - Walter Nobbe - Fabrizio Plessi - Paul Van Rafelghem - Maus Slangen - Douglas Swan - Walter Tafelmaier - Leo De Vries - Friso Wiegersma - Troels Worsel, Galerie Jurka, Amsterdam, 1976
Engels
boek